Knowledge Management Practices in Multinational Corporations - Ansar, Novera; Rizavi, Dr. Saqib (JISR management and social sciences & economics, 2012)
Knowledge management is an emerging concept yet it is a vast area where organizations are required to adopt most effective strategies in order to gain a competitive advantage. The aim of this study is to examine whether the multinational corporations (MNCs) dealing in fast-moving consumer goods (FMCG) practice the idea in its true sense and apply the concept for improving knowledge management. The study is exploratory in nature. The research instrument for this study is adopted from another study on knowledge management in German Industry. Due to the absence of a sampling frame a non-probability sampling method was required to be used therefore; purposive sampling method is used by selecting five FMCG multinational corporations. The is analyzed descriptively by using Statistical Package for the Social Sciences (SPSS).The analysis shows that the biggest hurdle towards knowledge management lies within the organizations since the organizations are protective towards knowledge and fear the loss of critical information to the competitors.